TORSI DAN DAYA SEPEDA MOTOR MATIC 4 TAK HASIL KEMIRINGAN SUDUT DRIVE PULLEY - Rifdarmon Rifdarmon; Prima Nefri Zofa; Erzeddin Alwi; Donny Fernandez (Ensiklopedia Education Review, 2022)
This study tries to ascertain how modifications in the Drive Pulley's inclination angle on automated bikes affect changes in torque and power output. With alterations to the Primary Sliding Shave and Primary Fixed Shave angles of 13.5o, 14.5o, and the conventional angle of 15o, the experimental research method employed in this study intends to examine the outcomes produced from variations on the same item as the research variable. According to the research, each variable experiences an average rise in torque with a value of 9.25 N/m and power with a value of 8.16 HP when the slope angle of each variable is changed. Only 7.9 N/m of torque and 7 HP are displayed in the results of the standard test. The torque and power produced by a 4 stroke automatic motorcycle may therefore be significantly increased by changing the tilt angle of the Primary Sliding Shave and Primary Fixed Shave.Keywords: Drive Pulleys, Tilt Angle, Torque and Power